Implementation of the POE2WE Learning Model to Improve Critical Thinking and Report Writing Skills - Siti Haryanti , Ade; Youlinda Parwis, Friza (IJORER : International Journal of Recent Educational Research, 2025)
Objective: This research aims to determine the effectiveness of POE2WE learning model to improving critical thinking and report writing skills. Method: This research used classroom action research. Data collection used tests and non-tests. The sample of this research was 40 Indonesian Language Education students at Indraprasta PGRI University, Jakarta. Results: The research in cycle 1 and cycle 2 showed a significant increase in critical thinking and report writing skills using the POE2WE learning model. Novelty: The novelty of this research lies in the POE2WE learning model to improve critical thinking and report writing skills, thus giving rise to a new trend regarding awareness of the use of innovative and unique learning models, and providing researchers with an overview of future research opportunities related to effective and efficient learning models.